2014
DOI: 10.1080/17441692.2014.967709
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent use of traditional medicine and ART: Perspectives of patients, providers and traditional healers in Durban, South Africa

Abstract: The concurrent use of traditional African medicine (TAM) and allopathic medicine is not well understood for people living with HIV (PLHIV) in the era of antiretroviral therapy (ART). This cross-sectional, qualitative study examines perceptions of the concurrent use of TAM and ART among: i) patients receiving ART at the Sinikithemba HIV Clinic of McCord Hospital, in Durban, South Africa; ii) allopathic medical providers (doctors, nurses, HIV counsellors) from Sinikithemba; and iii) local traditional healers. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 36 publications
1
41
0
Order By: Relevance
“…Traditional forms of illness are understood to result from supernatural causes such as bewitchment or ancestral wrath [41,65,66]. Healing of illness largely involves divination, faith healing and traditional medicinal remedies [6769].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Traditional forms of illness are understood to result from supernatural causes such as bewitchment or ancestral wrath [41,65,66]. Healing of illness largely involves divination, faith healing and traditional medicinal remedies [6769].…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted in KwaZulu-Natal found that, out of 11 THPs participating in the study, none said that they could cure HIV. A predominant belief among these THPs was that they could help patients with symptoms of HIV [41]. Other studies had previously suggested that THPs thought they could cure HIV/AIDS through different rituals and healing practices [49,65,74,75].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, shifting to a chronic disease model of HIV care and facilitating ART initiation in both symptomatic and asymptomatic patients would benefit long-term engagement in care. Through the expansion of home-based care interventions (Decroo et al, 2014; Grimsrud, Lesosky, Kalombo, Bekker, & Myer, 2015), CHWs are uniquely positioned to help mitigate barriers to care such as stigma, denial, inadequate patient education, poor social support (Root & Whiteside, 2013; Zulliger et al, 2014), and patient preferences for alternative medicine (Appelbaum Belisle et al, 2015; Peltzer, Friend-du Preez, Ramlagan, Fomundam, & Anderson, 2010). …”
Section: Discussionmentioning
confidence: 99%